2018
DOI: 10.3390/en11010155
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Electrical Characterization of a Semi-Transparent Dye-Sensitized Photovoltaic Module under Real Operating Conditions

Abstract: Dye-sensitized solar cell technology is having an important role in renewable energy research due to its features and low-cost manufacturing processes. Devices based on this technology appear very well suited for integration into glazing systems due to their characteristics of transparency, color tuning and manufacturing directly on glass substrates. Field data of thermal and electrical characteristics of dye-sensitized solar modules (DSM) are important since they can be used as input of building simulation mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…They found that while the thermal transmittance (U-value) was similar, cells with a lower g-value (SHGC), demonstrated strong correlation between the thickness of a-Si layers and energy conservation in lower latitudes. In another study, Martin-Chivelet et al [27] concluded that the degree of transparency of PV modules had 'no appreciable influence' on thermal transmittance (U-value), whereas differences associated with SHGC (g-value) were noted.…”
Section: Solar Heat Gain (G-value)mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that while the thermal transmittance (U-value) was similar, cells with a lower g-value (SHGC), demonstrated strong correlation between the thickness of a-Si layers and energy conservation in lower latitudes. In another study, Martin-Chivelet et al [27] concluded that the degree of transparency of PV modules had 'no appreciable influence' on thermal transmittance (U-value), whereas differences associated with SHGC (g-value) were noted.…”
Section: Solar Heat Gain (G-value)mentioning
confidence: 99%
“…As noted previously, the semi-transparency of 'crystalline silicon PV arrays is created by the transparent glazing surrounding the opaque solar cells, whereas thin-film technologies achieve semi-transparency by using laser ablation to remove layers of the substrate. For this reason, assessing the thermal performance of semi-transparent BIPV is a relatively complex matter, with standard methods designed for conventional glazing potentially producing erroneous results [27,28]. Both the U-value, which measures heat transmission through the BIPV-module and can be calculated using the equations in [29], and the 'solar heat gain coefficient' (SHGC), also known as the g-value, which measures the amount of heat transmitted into the building due to solar radiation, need to be taken into account [26].…”
Section: Thermal Performancementioning
confidence: 99%
“…Nuria [7] installed photovoltaic windows in a room, and obtained decreased energy consumption. Cristina Cornaro et al [8] invented dye-sensitized solar cells and tested it for its electrical and thermal properties. Dye-sensitized solar cells play an important role in renewable energy research due to its features and low-cost manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Their market share is unknown, but the share of all thin-film solar modules is around 10-15% [1, [10][11][12]16,17]. A special type of the thin-film technology, called dye-sensitized solar cells, have an important role in renewable energy-related research activity due to their features and low-cost manufacturing processes [18]. Research projects in Hungary were conducted with silicon-based thin film and crystalline photovoltaic technologies which have been rapidly expanding, are relatively inexpensive, and have a growing market share.…”
Section: Introductionmentioning
confidence: 99%